KESALAHPAHAMAN TERHADAP PEMAKNAAN SURAH AL AHZAB AYAT 59: MAKNA JILBAB DAN TUJUAN PERLINDUNGAN - Maulida, Rizky; Huda, Ahmad Nawirul; Adyaksa, Adyaksa; Cholil, Mufidah (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2025)
This study aims to examine the meaning and purpose of the command to wear hijab in Surah Al-Ahzab verse 59, focusing on the function of hijab as a form of protection and identity for Muslim women. This research is a library research with a qualitative approach. Data was collected through an in-depth study of classical and contemporary interpretive literature, as well as relevant Islamic sources such as hadiths, scholarly works, and related scientific articles. The data analysis technique used is content analysis, which focuses on interpreting the text contextually and historically to explore the substantive meaning of the verse. To maintain the validity of the data, source triangulation is carried out, interpretation validation through comparison between interpretations, and checking the compatibility of meaning in the current social context. interpretation, increase awareness of Islamic values in dressing, and encourage the creation of just social harmony. The results of the study show that there is a narrowing of the meaning of the term hijab, which is often understood only as a head covering or a certain form of clothing, while the main message of the verse is politeness and social protection. In the current context, the hijab remains relevant as a symbol of obedience, respect, and protection from objectification. By understanding the historical and social context of this verse, this research seeks to bridge differences in interpretation, increase awareness of Islamic values in dress, and encourage the creation of just social harmony.